menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
Let f(x) = -x-1, h(x) = x-3/3 Find (f o h)(-1).
asked
Jan 6, 2022
115k
views
7
votes
Let f(x) = -x-1, h(x) = x-3/3
Find (f o h)(-1).
Mathematics
high-school
Shalev Shalit
asked
by
Shalev Shalit
5.3k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
4
votes
(f o h) = -(x - 3/3) - 1
(f o h) = (-x + 3)/3 - 1
(f o h)(1) = (-1 + 3)/3 - 1
(f o h)(1) = 2/3 - 1
(f o h)(1) = -1/3
Jamie Czuy
answered
Jan 11, 2022
by
Jamie Czuy
4.7k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.6m
questions
7.3m
answers
Other Questions
What is the value of x? (-4) - x = 5
1/7 + 3/14 equivalent fractions
185g in the ratio 2:3
(3x1,000,000)+(3x100,000)+(2x100) what is this number written in standard form?
The function h = -t2 + 95 models the path of a ball thrown by a boy where h represents height, in feet, and t represents the time, in seconds, that the ball is in the air. Assuming the boy lives at sea
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org